2023
DOI: 10.3389/fphar.2023.1297931
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuroinflammation in the transition of acute to chronic pain and the opioid-induced hyperalgesia and tolerance

Marco Echeverria-Villalobos,
Victor Tortorici,
Beatriz E. Brito
et al.

Abstract: Current evidence suggests that activation of glial and immune cells leads to increased production of proinflammatory mediators, creating a neuroinflammatory state. Neuroinflammation has been proven to be a fundamental mechanism in the genesis of acute pain and its transition to neuropathic and chronic pain. A noxious event that stimulates peripheral afferent nerve fibers may also activate pronociceptive receptors situated at the dorsal root ganglion and dorsal horn of the spinal cord, as well as peripheral gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 154 publications
(199 reference statements)
0
4
0
Order By: Relevance
“…Firstly, the spinal cord plays a vital role in pain signal transmission, and the L4-L6 section is commonly used in neuropathic pain related to nerve injury or CIPN studies [28,29]. The transition from acute to chronic pain involves central neuroinflammation mechanisms like glial activation [30], and we used a chronic oxaliplatin-induced CIPN model in this research. Secondly, previous RgIA results showed that the peripherally acting α9α10 nAChR antagonist could affect CNS glial cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the spinal cord plays a vital role in pain signal transmission, and the L4-L6 section is commonly used in neuropathic pain related to nerve injury or CIPN studies [28,29]. The transition from acute to chronic pain involves central neuroinflammation mechanisms like glial activation [30], and we used a chronic oxaliplatin-induced CIPN model in this research. Secondly, previous RgIA results showed that the peripherally acting α9α10 nAChR antagonist could affect CNS glial cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…From a pathophysiological point of view, the benefits of an extended treatment with oral micron-size PEA in chronic pain may be explained by considering the specific role of the neuroinflammation in promoting and maintaining pain in different conditions. It is well known that neuroinflammation plays a key role in the onset and evolution of chronic pain and probably also in the transition from acute to chronic pain [ 64 ]. In fact, the so-called “non-neuronal cells” (microglia and mast cells) are considered the main responsible actors of this process [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation is characterized by an inflammatory response occurring within the central nervous system (CNS) as a result of both exogenous and endogenous factors [ 20 ]. It is an inflammatory cascade reaction involving various immune cells and/or molecules [ 21 ].…”
Section: Neuroinflammationmentioning
confidence: 99%